Model Pembelajaran Kooperatif dalam Menumbuhkan Keaktifan Siswa terhadap Pembelajaran IPS - Antika, Defi; Yusnaldi, Eka; Khairunnisa, Khairunnisa; Sakinah, Nurul; Azhari, Wahyu; Deliyanti, Yuli (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to describe the Cooperative Learning Model in Fostering Student Engagement in Social Studies Learning. This research uses qualitative descriptive research with literature study, which collects information and related scientific writings. This research also presents data without any manipulation and additional treatment. The main source of this research is previous scientific writings closely related to literature study, such as research method books, journal articles, internet articles, and other relevant writings. The results of the study show that the use of cooperative learning models is expected to improve the quality of education without making students bored and tired of the learning process, especially in increasing students' engagement with the material presented in class.